Four new orchid species from the Lengguru fold belt, West Papua, Indonesia - Juswara, L.; Schuiteman, A.; /Droissart, Vincent (2016)
Bulbophyllum leucoglossum, Dendrobium centrosepalum, Dendrobium taeniocaule, and Taeniophyllum pyriforme are here described as new species, based on herbarium specimens collected from the Lengguru fold-and-thrust belt in the West Papua Bird's neck, Indonesian New Guinea. All four novelties were found growing in submontane forest (elevation > 1000 m a.s.l.) on limestone karst. Information concerning the distribution and habitat for these taxa is provided along with diagnostic features, line drawings, high resolution photographs, and a map of collecting localities. More field studies are required to find additional populations of these new species, in order to better characterize their habitat, ecology and conservation status.